Wybrane kody kulturowe w sprawozdaniach z podróży do wód akwizgrańskich Józefa Sapiehy oraz Ignacego Łopacińskiego w 1740 r. - Kucharski, Adam (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny)
In the present paper, the concept of cultural codes was employed for research on travels abroad of the elites of Polish-Lithuanian Commonwealth. In accordance with the assumptions of travel semiotics, the intellectual activity of travelers in the processes of knowing and describing the world constitutes a form of coding and deciphering meanings. Such understanding can be referred to both modern mass tourism and premodern types of travel (educational and curative travels or pilgrimages). The subject of this paper is the tourist-curative travel for the waters undertaken by the bishop of Vilnius (and simultaneously Grand Referendary of the Grand Duchy of Lithuania) Józef Stanisław Sapieha (1708–1754) and his companion, Ignacy Łopaciński.
Keywords: Józef Sapieha; Ignacy Łopaciński